Mastering Dreamweaver MX databases - Harkins, Susan Sales (SYBEX, 2003)
Mastering Dreamweaver MX Databases provides in-depth instruction and tutorials for designers and developers looking to create data-driven web pages with Dreamweaver MX. Where most books on this topic cover one or two databases, this title covers all major databases, languages, and development platforms, including Access, SQL Server, MySQL, Oracle, ColdFusion, JSP, ASP, ASP.NET, and ADO.NET.